The Effectiveness of Premarital Health Counseling on the Attitude of Prospective Brides in Preparing for a Healthy Pregnancy - Jihan Mentari Fitrah Rahmanda; Maryanah; Sri Mulyati (International Journal of Science and Society, 2023)
There are 51.4% of 1,928 people in their reproductive age in DKI Jakarta who do not know the need to conduct premarital health counseling for the bride, this shows the low essence of the implementation of counseling for prospective brides in preparing for a healthy pregnancy. The purpose of this study was to determine the effect of providing premarital health counseling on the bride-to-be, in preparing for a healthy pregnancy. This research method uses a pre-experiment method with one group pretest-posttest design. The subjects in this study were the bride aged 19 - 45 years who would do a health check at Puskesmas Tanjung Priok, with a total of 42 respondents. The sampling technique is purposive sampling. This research using dependent t-test for data analysis. The result is there is effectiveness in health counseling with p-value = 0,0001 (<0,005) that show significant difference on prospective bride’s attitude in preparing healthy pregnancy.